The Greenwood encyclopedia of Asian American literature [ - Huang, Guiyou , 1961- (The American mosaic, 2009)
Contains entries on topics in Asian American literature, including writers, special topics, events, and terms. Covers literature by North American writers of Asian descent from the late 1890s to 2007, within a variety of contexts